Strategi Manajemen Pengendalian Persediaan obat Hipertensi dan Diabetes Melitus di Puskesmas Cimahi Utara - Rahmayati, Anisa; Purwadhi, Purwadhi; Veranita, Mira (Masyarakat Ekonomi Syariah Bogor, 2025)
This research is motivated by the fact that problems are still found in the control of the supply of non-communicable disease drugs, especially Diabetes Mellitus (DM) and Hypertension (HT), at the North Cimahi Health Center, such as stock vacancies, excess of certain drugs, and limited use of information systems. The purpose of this study is to analyze the management strategy of drug inventory control, including the planning, organization, implementation, and control stages, as well as to evaluate the effectiveness of these strategies in supporting the sustainability of health services. This study uses a descriptive qualitative method with data collection techniques through interviews, observations, and documentation, and is analyzed using the Miles and Huberman interactive model. The results of the study show that drug needs planning is carried out based on monthly usage data and patient visit trends, but is still constrained by distribution quotas and budget allocation from the Health Office. The organizing strategy is carried out with a clear division of tasks between the heads of health centers, pharmacists, pharmacists, and administrative staff, and is supported by the use of e-catalogs. The implementation of the strategy involves manual and digital recording, the use of Economic Order Quantity (EOQ), Reorder Point (ROP), and Safety Stock methods to maintain inventory stability, although there are still obstacles in the form of demand fluctuations and distribution delays. The control process is carried out through daily monitoring, internal audits, and periodic reporting mechanisms to the Health Office, with contingency strategies in the form of restrictions on the administration of drugs or referring patients to external pharmacies. Overall, control strategies have proven effective for priority drugs such as Amlodipin and Metformin, but they still need to be strengthened for alternative drugs such as Glibenklamidi which are prone to vacuum. The conclusion of this study is that the implementation of strategic management in controlling drug inventory at the North Cimahi Health Center has supported the availability of the main drug, the sustainability of therapy, and patient satisfaction, although it still faces limited resources, external supply, and data accuracy. The implications of this study emphasize the need to optimize information systems, strengthen internal coordination, and increase strategic flexibility so that drug inventory control can be more adaptive, efficient, and sustainable.